2018
DOI: 10.1074/jbc.m117.818930
|View full text |Cite
|
Sign up to set email alerts
|

The cartilage-specific lectin C-type lectin domain family 3 member A (CLEC3A) enhances tissue plasminogen activator–mediated plasminogen activation

Abstract: C-type lectin domain family 3 member A (CLEC3A) is a poorly characterized protein belonging to the superfamily of C-type lectins. Its closest homologue tetranectin binds to the kringle 4 domain of plasminogen and enhances its association with tissue plasminogen activator (tPA) thereby enhancing plasmin production, but whether CLEC3A contributes to plasminogen activation is unknown. Here, we recombinantly expressed murine and human full-length CLEC3As as well as truncated forms of CLEC3A in HEK-293 Epstein-Barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…We identified a set of genes that are statistically differentially expressed only between chronic and acute lesions, while showing little changes between acute and nonlesional AD (Fig 2, B-D). These include genes that participate in skin barrier maintenance and repair (HRNR), IL-20, [14][15][16] immunoglobulin production (IGHG1, IGLC2, IGKC), inhibition of CD4 1 T-cell activation (CLEC3A), 17 and tryptophan metabolism (KYNU). 18 It is noteworthy that the immunoglobulins as a group have been identified as differentially expressed in chronic lesional skin of psoriasis and AD 8 ; in addition, KYNU, the L-kynureninase, which regulates tryptophan metabolism, can serve as an immune response modulator for chronic inflammatory conditions.…”
Section: Resultsmentioning
confidence: 99%
“…We identified a set of genes that are statistically differentially expressed only between chronic and acute lesions, while showing little changes between acute and nonlesional AD (Fig 2, B-D). These include genes that participate in skin barrier maintenance and repair (HRNR), IL-20, [14][15][16] immunoglobulin production (IGHG1, IGLC2, IGKC), inhibition of CD4 1 T-cell activation (CLEC3A), 17 and tryptophan metabolism (KYNU). 18 It is noteworthy that the immunoglobulins as a group have been identified as differentially expressed in chronic lesional skin of psoriasis and AD 8 ; in addition, KYNU, the L-kynureninase, which regulates tryptophan metabolism, can serve as an immune response modulator for chronic inflammatory conditions.…”
Section: Resultsmentioning
confidence: 99%
“…CLEC3A is a protein related to the great family of C-type lectins and can be seen in normal human breast tissue, but not in any other normal human tissue [15][16][17] . This protein is a heparin-binding, cell adhesion modulator that have capability to alter tumor cell invasion and metastasis by modulating tumor cell adhesion and the plasminogen/plasminogen-activator system [18] . Kallikreins are a subgroup of serine proteases, enzymes capable of cleaving peptide bonds in proteins, and a family of 15 genes on chromosome 19 [19] .…”
Section: Introductionmentioning
confidence: 99%
“… 14 Additionally, CLEC3A was reported to activate the plasminogen activation via enhancing tissue plasminogen activator. 15 It was found that plasminogen activator system was identified as one of the major mechanisms involved in the processes of cell invasion and metastatic spreading. 16 , 17 However, there is no direct evidence whether CLEC3A associates with clinicopathological significance in BC oncology and cancer progression.…”
Section: Introductionmentioning
confidence: 99%